PENGARUH KUALITAS ASET, RENTABILITAS, MODAL DAN LIKUIDITAS TERHADAP HARGA SAHAM BANK - Christie, Cicilia Novi Atika; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACT This research is meant to test the influence of assets, profitability, capital and liquidity to the stock price which are listed in the IDX. Assets in this research has been measured by using Non-Performing Loan ratio (NPL), profitability has been measured by using Return On Asset ratio (ROA) and Return On Equity (ROE), capital has been measured by using Capital Adequacy Ratio (CAR) and liquidity has been measured by using Loan to Deposit Ratio (LDR). This research has been carried out by using secondary data which includes 26 banking companies in 2012-2014 periods and it has been done by using purposive sampling technique. The data analysis technique has been carried out by using multiple linear regressions analysis. It has been found from the result of the analysis, that Non-Performing Loan (NPL) does not have any influence to the stock price; Return On Asset (ROA) has positive influence to the stock price; Return On Equity (ROE) does not have any influence to the stock price; Capital Adequacy Ratio (CAR) has negative influence to the stock price; Loan to Deposit Ratio (LDR) does not have any influence to the stock price. Keywords: Non performing loan, profitability, capital adequacy ratio, loan to deposit ratio , stock price.